Modified SBR binder and preparation method thereof

By preparing a modified SBR binder with a specific chemical general and structure, the existing SBR adhesive preparation process is complex, poor adhesive, and poor low temperature adaptability. Low temperature tolerance and reduced preparation costs.

CN119331540APending Publication Date: 2025-01-21EVE POWER CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411458580.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The preparation process of existing SBR adhesives is complex, has poor adhesion, and has poor adaptability to low temperatures.

Method used

A modified SBR binder, its chemical formula is a specific agglomeration and amide -type compound co -cross -crossing structure in a specific polymerization and molecular weight range. The group, as well as some surfactants, are legally prepared through the lotion.

Benefits of technology

It is realized that the modified SBR binder has excellent adhesion, mechanical strength and low temperature tolerance, and at the same time, the preparation method is simple and the cost is low.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331540A_ABST
    Figure CN119331540A_ABST
Patent Text Reader

Abstract

The invention provides a modified SBR (Styrene Butadiene Rubber) binder and a preparation method thereof. The chemical general formula of the modified SBR binder is as follows: # imgabs0 #, a, b, c and x are respectively and independently polymerization degrees, a is 10000 to 12000, b is 15000 to 20000, c is 13000 to 18000, and x is 1 to 15. The modified SBR binder with the chemical general formula has a structure similar to a core-shell, the interior of the shell is a cross-linked structure of styrene and an amide compound copolymer molecular chain, and the exterior of the shell is hydrophilic polar groups corresponding to butadiene and rigid monomers and part of the surface active agent. The modified SBR binder with the structure has excellent cohesiveness, mechanical strength and low-temperature tolerance, and the preparation method is simple and low in cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of binders, and in particular to a modified SBR binder and a preparation method thereof. Background Art

[0002] As people continue to conduct in-depth research on lithium-ion batteries, many achievements have been made in terms of battery safety performance, rate performance, cycle performance, capacity performance, high and low temperature performance, assembly performance, etc. With the development of lithium-ion batteries, people's performance requirements are not limited to high energy density, and fast charging is also one of the key evaluation criteria. At present, the main method to reduce the amount of binder and conductive agent without adversely affecting the performance of the battery is to develop a new binder and conductive agent system, that is, to use a binder with better adhesion or add a conductive material with better conductivity.

[0003] In a Chinese patent application with a patent application publication number of CN 108598482 A, a carbon black modified water-based SBR lithium-ion battery binder is proposed. The carbon black modified water-based SBR lithium-ion battery binder is made of styrene and butadiene as raw materials, and conductive carbon black is bonded to the SBR molecular chain by an in-situ emulsion polymerization method. The method has a complex synthesis process and a low yield, which is not conducive to large-scale preparation.

[0004] In a Chinese patent application with the publication number of CN 114478898 A, an emulsion polymerization adhesive for replacing SBR for a negative electrode of a lithium battery and a preparation method thereof are provided. First, monomers are selected that are very stable and reliable after polymerization, and cross-linking and electrolyte absorption are moderate to maintain the stability of the framework of the negative electrode layer for receiving and releasing lithium ions. In addition, an emulsifier that is valence-bonded to the polymer is selected so that all polymer adhesives are a complete body without excess impurities. The adhesive prepared by this method has a high glass transition temperature and is suitable for natural graphite. For artificial graphite with high hardness, the adhesive performance is low, which affects the cycle performance. Summary of the invention

[0005] The main purpose of the present invention is to provide a modified SBR binder and a preparation method thereof, so as to solve the problems of the SBR binder in the prior art, namely, complicated preparation process, poor adhesion and poor adaptability to low temperature.

[0006] In order to achieve the above object, according to one aspect of the present invention, a modified SBR binder is provided, and the chemical formula of the modified SBR binder is as follows:

[0007]

[0008] wherein a, b, c and x are each independently a degree of polymerization, a is 10,000 to 12,000, b is 15,000 to 20,000, c is 13,000 to 18,000, and x is 1 to 15.

[0009] Furthermore, the molecular weight of the modified SBR binder is 400,000 to 600,000.

[0010] Furthermore, the modified SBR binder is in the form of latex particles, and preferably the particle size of the latex particles is 50 to 150 nm.

[0011] According to another aspect of the present invention, a method for preparing the aforementioned modified SBR binder is provided, the method comprising: step S1, mixing raw materials including an emulsion, styrene, a first initiator and an amide compound, and then performing a first polymerization reaction to obtain a first polymer intermediate; step S2, performing a second polymerization reaction on raw materials including the first polymer intermediate, a deoxidizer, a second initiator, butadiene and a rigid monomer to obtain a product system; step S3, post-treating the product system to obtain a modified SBR binder; wherein the rigid monomer is a cycloalkyl-substituted organic carboxylic acid.

[0012] Furthermore, in the above step S1, the temperature of the first polymerization reaction is 50-80°C, and / or the time of the first polymerization reaction is 1.5-4h; and / or the first initiator is peroxybenzoic acid ester and / or diisopropyl peroxydicarbonate; and / or the emulsion comprises an emulsifier and water, and the mass ratio of water to emulsifier is (200-400):(0.1-0.5), preferably (300-350):(0.2-0.4); preferably, the emulsifier is selected from any one or more of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, fatty acid soap, quaternary ammonium salt and polyol fatty acid ester; preferably, the mass ratio of the emulsifier to the first initiator is (0.1-0.5):(0.5-1.0).

[0013] Furthermore, in the above step S2, the temperature of the second polymerization reaction is 70 to 90° C., and / or the time of the second polymerization reaction is 2 to 4 hours; and / or the cycloalkyl substituent in the rigid monomer is C3 to C 10 The cycloalkyl group is preferably a C3-C6 cycloalkyl group, preferably a C5-C6 cycloalkyl group. Further, the rigid monomer is preferably a formic acid substituted with a C5-C6 cycloalkyl group. Further, the rigid monomer is preferably selected from any one or more of pipecolic acid, L-proline, and 2-aminocyclohexanecarboxylic acid.

[0014] Furthermore, in the above step S2, the mass ratio of styrene, butadiene, amide compounds and rigid monomers is (20-25): (10-15): (1-3): (0.1-0.5), preferably (22-24): (12-13): (1.5-2.0): (0.2-0.3).

[0015] Furthermore, the molecular weight of the amide compound is 101-300, and the amide compound is preferably selected from any one or more of N-hydroxymethyl acrylamide, N-hydroxyethyl acrylamide, N-hydroxypropyl acrylamide and N-hydroxybutyl acrylamide.

[0016] Furthermore, the above-mentioned deoxidizer is bleaching powder; and / or the mass ratio of the deoxidizer to the second initiator is (0.5-1.0):(0.5-2.0); and / or the second initiator is azobisisobutyl cyanide and / or azobisisoheptanenitrile; and / or the mass ratio of the second initiator to the rigid monomer is (0.5-2):(5-10).

[0017] Furthermore, the above post-treatment is an extraction treatment.

[0018] By applying the technical solution of the present invention, the modified SBR binder having the above chemical formula has a core-shell structure, wherein the inside of the shell is a cross-linked structure of the copolymer molecular chains of styrene and amide compounds, and the outside of the shell is a hydrophilic polar group corresponding to butadiene and a rigid monomer, as well as some surfactants. The modified SBR binder having the above structure of the present application has excellent adhesion, mechanical strength and low temperature tolerance, and the above preparation method is simple and the cost is low. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0020] Figure 1 The infrared test result graph of the modified SBR binder obtained in Examples 1 to 3 and Examples 7 to 9 of the present application is shown. DETAILED DESCRIPTION

[0021] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0022] As analyzed in the background technology of this application, there are problems in the prior art such as complex preparation process, poor adhesion and poor adaptability to low temperatures of SBR binders. In order to solve the above problems, this application provides a modified SBR binder and a preparation method thereof.

[0023] In a typical embodiment of the present application, a modified SBR binder is provided, and the chemical formula of the modified SBR binder is as follows:

[0024]

[0025] wherein a, b, c and x are each independently a degree of polymerization, a is 10,000 to 12,000, b is 15,000 to 20,000, c is 13,000 to 18,000, and x is 1 to 15.

[0026] The modified SBR binder with the above chemical formula has a core-shell structure, wherein the inside of the shell is a cross-linked structure of styrene and amide compound copolymer molecular chains, and the outside of the shell is a hydrophilic polar group corresponding to butadiene and a rigid monomer, as well as some surfactants. The modified SBR binder with the above structure of the present application has excellent adhesion, mechanical strength and low temperature tolerance, and the above preparation method is simple and low cost.

[0027] In one embodiment of the present application, the molecular weight of the modified SBR binder is 400,000 to 600,000.

[0028] The modified SBR binder having the above molecular weight has a more suitable viscosity, thereby facilitating its use in the process.

[0029] In one embodiment of the present application, the modified SBR binder is in the form of latex particles, and preferably the particle size of the latex particles is 50 to 150 nm.

[0030] The modified SBR binder with the above particle size has a larger specific surface area due to the latex particles, which is conducive to making it have better bonding properties.

[0031] In another typical embodiment of the present application, a method for preparing the aforementioned modified SBR binder is provided, the method comprising: step S1, mixing raw materials including an emulsion, styrene, a first initiator and an amide compound, and then performing a first polymerization reaction to obtain a first polymer intermediate; step S2, performing a second polymerization reaction on raw materials including the first polymer intermediate, a deoxidizer, a second initiator, butadiene and a rigid monomer to obtain a product system; step S3, post-treating the product system to obtain a modified SBR binder; wherein the rigid monomer is a cycloalkyl-substituted organic carboxylic acid.

[0032] Through the different steps of adding the above monomers and the order of sequential polymerization, the latex particles of the modified SBR binder obtained in the present application have a core-shell structure, wherein the inside of the shell is a cross-linked structure of the copolymer molecular chains of styrene and amide compounds, and the outside of the shell is the hydrophilic polar groups corresponding to butadiene and the rigid monomer, as well as some surfactants. The modified SBR binder having the above structure of the present application has excellent adhesion, mechanical strength and low-temperature tolerance, and the above preparation method is simple and low-cost.

[0033] In one embodiment of the present application, in the above-mentioned step S1, the temperature of the first polymerization reaction is 50-80°C, and / or the time of the first polymerization reaction is 1.5-4h; and / or the first initiator is peroxybenzoic acid ester and / or diisopropyl peroxydicarbonate; and / or the emulsion includes an emulsifier and water, and the mass ratio of water to emulsifier is (200-400): (0.1-0.5), preferably (300-350): (0.2-0.4); preferably, the emulsifier is selected from any one or more of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, fatty acid soap, quaternary ammonium salt and polyol fatty acid ester; preferably, the mass ratio of the emulsifier to the first initiator is (0.1-0.5): (0.5-1.0).

[0034] The preferred temperature and time of the first polymerization reaction are within the above ranges, which helps to improve the efficiency and effect of the first polymerization reaction. The preferred emulsifier and its volume ratio to water are within the above ranges, which helps to make the emulsion reach a suitable concentration range. The preferred first initiator is conducive to improving the effect of the first polymerization reaction.

[0035] In one embodiment of the present application, in the above step S2, the temperature of the second polymerization reaction is 70-90° C., and / or the time of the second polymerization reaction is 2-4 hours; and / or the cycloalkyl substituent in the rigid monomer is C3-C 10 The cycloalkyl group is preferably a C3-C6 cycloalkyl group, preferably a C5-C6 cycloalkyl group. Further, the rigid monomer is preferably a formic acid substituted with a C5-C6 cycloalkyl group. Further, the rigid monomer is preferably selected from any one or more of pipecolic acid, L-proline, and 2-aminocyclohexanecarboxylic acid.

[0036] The preferred temperature and time of the second polymerization reaction are within the above ranges, which helps to improve the efficiency and effect of the second polymerization reaction. By introducing cyclic groups into the side chains of the above rigid monomers, at low temperatures, the SBR film covers the surface of the graphite, and Li + During transmission, it is promoted to bypass the modified SBR membrane to reach the surface of graphite, and the introduction of rigid cyclic groups is beneficial to increase the mechanical strength of the binder SBR, enhance the elastic modulus of the modified SBR binder, and promote Li + Conduction.

[0037] In one embodiment of the present application, in the above step S2, the mass ratio of styrene, butadiene, amide compounds and rigid monomers is (20-25): (10-15): (1-3): (0.1-0.5), preferably (22-24): (12-13): (1.5-2.0): (0.2-0.3).

[0038] The preferred mass ratio of the above substances is helpful to improve the synergistic effect between the monomers, thereby obtaining a modified SBR binder with a suitable molecular weight and a suitable amount of functional groups.

[0039] In one embodiment of the present application, the molecular weight of the amide compound is 101-300, and the amide compound is preferably selected from any one or more of N-hydroxymethyl acrylamide, N-hydroxyethyl acrylamide, N-hydroxypropyl acrylamide and N-hydroxybutyl acrylamide.

[0040] The preferred amide compounds of the above types have strong electronegativity, which helps to increase the crosslinking degree within the latex particle shell of the modified SBR binder and enhance the cohesive force of the binder SBR, thereby facilitating good contact between the negative electrode material and the current collector and promoting Li + On the other hand, there are lone pairs of electrons in the above amide substances with strong electronegativity, which can continuously react with Li under the action of electric field. + Complexation and decomplexation reactions occur, which is beneficial to Li + diffusion.

[0041] In one embodiment of the present application, the above-mentioned deoxidizer is bleaching powder; and / or the mass ratio of the deoxidizer to the second initiator is (0.5-1.0):(0.5-2.0); and / or the second initiator is azobisisobutyl cyanide and / or azobisisoheptyl cyanide; and / or the mass ratio of the second initiator to the rigid monomer is (0.5-2):(5-10).

[0042] The dissolved oxygen in water has an inhibitory effect at low temperatures. The preferred deoxidizer and the mass ratio range of the deoxidizer to the second initiator help it to react more fully with the dissolved oxygen in water, thereby promoting the normal progress of the polymerization reaction. The preferred second initiator and the mass ratio range of the second initiator to the rigid monomer are conducive to further promoting the occurrence of the second polymerization reaction.

[0043] In one embodiment of the present application, the above-mentioned post-treatment is an extraction treatment.

[0044] The above preferred method can simplify the post-treatment process and help to reduce the content of impurities in the product as much as possible. Further, toluene is preferably used as the extractant.

[0045] The beneficial effects of the present application will be further illustrated below in conjunction with embodiments.

[0046] Example 1

[0047] Step 1, emulsion preparation: add a certain amount of water and emulsifier (sodium dodecylbenzene sulfonate) into a three-necked flask and place it in a constant temperature water bath at 30°C. Use condensed N2 as protective gas. Turn on the magnetic stirrer for 30 minutes at a speed of 280-400 rpm. Wait until the emulsifier is completely dissolved to obtain an emulsion in which the volume ratio of water to emulsifier is 300:0.2.

[0048] Step 2, preparing seed particles: taking a mixed solution of styrene and N-hydroxymethyl acrylamide, continuously dropping it into the emulsion prepared in step 1 to carry out a first polymerization reaction, taking peroxybenzoate and adding it to the first polymerization reaction system, the temperature of the first polymerization reaction is 80°C, the time of the first polymerization reaction is 1.5h, the dripping speed of the emulsion is controlled to be 0.5mL / s, and the reaction is terminated when no oil droplets appear in the three-necked flask, wherein the mass ratio of sodium dodecylbenzene sulfonate to N-hydroxymethyl acrylamide is 0.2:0.5.

[0049] Step 3, particle growth: After step 2 is completely reacted, continue to add emulsion to the three-necked flask, introduce nitrogen protection, and add a small amount of bleaching powder to the system; add oily initiator (azobisisobutyl cyanide), butadiene, and pipecolic acid to the three-necked flask respectively for a second polymerization reaction. The temperature of the second polymerization reaction is 90° C., and the time of the second polymerization reaction is 2h. Among them, the mass ratio of styrene, butadiene, N-hydroxymethyl acrylamide and pipecolic acid is 22:12:1.5:0.2, the mass ratio of bleaching powder and azobisisobutyl cyanide is 0.5:0.5, and the mass ratio of azobisisobutyl cyanide and pipecolic acid is 0.5:5.

[0050] Step 4, extraction and purification: Using toluene as an extractant, the emulsion obtained in step 3 is extracted and purified to obtain a low-temperature and high-rate modified SBR binder for lithium batteries. The infrared test results are shown in the attached Figure 1 (Scheme 1).

[0051] Example 2

[0052] The difference from Example 1 is that the rigid monomer is L-proline, and the modified SBR binder is finally obtained. The infrared test results are shown in the attached Figure 1 (Scheme 2).

[0053] Example 3

[0054] The difference from Example 1 is that the rigid monomer is 2-aminocyclohexanecarboxylic acid, and the modified SBR binder is finally obtained. The infrared test results are shown in the attached Figure 1(Scheme 3).

[0055] Example 4

[0056] The difference from Example 1 is that the mass ratio of styrene, butadiene, N-hydroxymethyl acrylamide and piperidine carboxylic acid is 24:13:2.0:0.3, and a modified SBR binder (Scheme 4) is finally obtained.

[0057] Example 5

[0058] The difference from Example 1 is that the mass ratio of styrene, butadiene, N-hydroxymethyl acrylamide and piperidine carboxylic acid is 20:10:1:0.1, and a modified SBR binder is finally obtained (Scheme 5).

[0059] Example 6

[0060] The difference from Example 1 is that the mass ratio of styrene, butadiene, N-hydroxymethyl acrylamide and piperidine carboxylic acid is 25:15:3:0.5, and a modified SBR binder is finally obtained (Scheme 6).

[0061] Example 7

[0062] The difference from Example 1 is that the amide compound is N-hydroxyethyl acrylamide, and the modified SBR binder is finally obtained. The infrared test results are shown in the attached Figure 1 (Scheme 7).

[0063] Example 8

[0064] The difference from Example 1 is that the amide compound is N-hydroxypropyl acrylamide, and the modified SBR binder is finally obtained. The infrared test results are shown in the attached Figure 1 (Scheme 8).

[0065] Example 9

[0066] The difference from Example 1 is that the amide compound is N-hydroxybutyl acrylamide, and the modified SBR binder is finally obtained. The infrared test results are shown in the attached Figure 1 (Scheme 9).

[0067] Example 10

[0068] The difference from Example 1 is that the mass ratio of bleaching powder to azobisisobutyl cyanide is 1:2, and the mass ratio of azobisisobutyl cyanide to pipecolic acid is 2:10, and finally a modified SBR binder is obtained (Scheme 10).

[0069] Embodiment 11

[0070] The difference from Example 1 is that the volume ratio of water to emulsifier is 350:0.4, and a modified SBR binder (Scheme 11) is finally obtained.

[0071] Example 12

[0072] The difference from Example 1 is that the volume ratio of water to emulsifier is 200:0.4, and a modified SBR binder (Scheme 12) is finally obtained.

[0073] Comparative Example 1

[0074] The difference from Example 1 is that no rigid monomer is added, and a modified SBR binder is finally obtained.

[0075] Comparative Example 2

[0076] The difference from Example 1 is that formic acid is used instead of pipecolic acid, and a modified SBR binder is finally obtained.

[0077] Performance Test:

[0078] Preparation of positive electrode sheet: lithium iron phosphate, conductive agent Super P, adhesive PVDF and polyvinyl pyrrolidone were mixed with water in a mass ratio of 97.5:0.5:1:1 to make a lithium-ion battery positive electrode slurry with a certain viscosity and a solid content of 50%. The slurry was coated on the aluminum foil for current collector with a coating amount of 360g / m 2 , dried at 85°C and then cold pressed; then striped and sliced, and then baked at 85°C in vacuum for 4 hours to make a lithium-ion battery positive electrode that meets the requirements.

[0079] Preparation of the negative electrode sheet: artificial graphite, conductive agent Super P, dispersant CMC, adhesive SBR (prepared by any embodiment or any comparative example of the present application) are mixed with N-methylpyrrolidone in a mass ratio of 96:0.8:1.5:1.7 to make a slurry, and mix them evenly. The solid content is 68%. The mixed slurry is coated on both sides of the copper foil, and then dried and rolled to obtain a negative electrode sheet, which is then baked at 85°C in vacuum for 4 hours to obtain a lithium ion battery negative electrode sheet that meets the requirements.

[0080] Preparation of electrolyte: Ethylene carbonate (EC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) are mixed in a mass ratio of 5:3:2, and after mixing, 1 mol of lithium hexafluorophosphate (LiPF6) electrolyte (100 g) is added, followed by 1 wt% of vinylene carbonate (based on the total mass of the electrolyte) and 1 wt% of lithium tetrafluoroborate.

[0081] Preparation of lithium-ion secondary batteries: The positive electrode sheet, negative electrode sheet and separator (polyethylene film coated ceramic separator) prepared according to the above process are made into a lithium-ion battery with a thickness of 0.5 mm, a width of 8 mm, and a length of 10 mm through a lamination process. The capacity is 3Ah, and the battery is vacuum-baked at 85°C for 48 hours, and the above-mentioned electrolyte is injected. The production of 3Ah soft-pack lithium-ion batteries is completed through the processes of packaging, shelving, formation, aging, secondary packaging and capacity division.

[0082] (I) Low temperature storage performance test of modified SBR binder

[0083] At 25°C, the lithium ion secondary batteries corresponding to the above embodiments and comparative examples are first charged to 3.65V with a constant current of 1C, further charged to a current of 0.05C with a constant voltage of 3.65V, and then discharged to 2.5V with a constant current of 1C. The discharge capacity of this time is the discharge capacity of the lithium ion secondary battery before low-temperature storage; then the lithium ion secondary battery is charged to 3.65V with a constant current of 1C, and the lithium ion secondary battery is stored at 0°C for 30 days. After the storage is completed, the lithium ion secondary battery is placed in an environment of 25°C, and then discharged to 2.5V with a constant current of 0.5C, then charged to 3.65V with a constant current of 1C, further charged to a current of 1C with a constant voltage of 3.65V, and then discharged to 2.5V with a constant current of 1C. The last discharge capacity is the discharge capacity of the lithium ion secondary battery after low-temperature storage. Capacity retention rate of lithium ion secondary battery after low-temperature storage (%)=[discharge capacity of lithium ion secondary battery after low-temperature storage / discharge capacity of lithium ion secondary battery before low-temperature storage]×100%.

[0084] (II) Low temperature rate performance test of modified SBR binder

[0085] The lithium ion secondary batteries of the above embodiments and comparative examples were tested for their charge and discharge capacities at 0.5C, 1C, and 2C at 0°C, and their capacity retention rates were calculated. The test method is as follows:

[0086] 1. Pretreatment at room temperature, the steps are as follows:

[0087] 1. Standard discharge: The battery is discharged at a constant current of 0.5C (A) to 2.5V;

[0088] 2. Let stand for 5 minutes;

[0089] 3. The battery is charged at a constant current and constant voltage of 0.5C (A), with a cut-off voltage of 3.65V and a cut-off current of 0.05C (A) for 10 cycles. The last discharge capacity is taken as the initial capacity and recorded as Q0.

[0090] 2. 1. Set different temperatures to 0±2℃ and leave for 0.5h;

[0091] 2. Discharge at different rates (0.5C, 1C, 2C) with a cut-off voltage of 2.5V;

[0092] 3. Record the discharge capacity Q2 of the battery and calculate the capacity retention rate = Q2 / Q0; the results are shown in Table 1.

[0093] The lithium ion secondary batteries of the above embodiments and comparative examples were tested for their charge and discharge capacities at 0.5C, 1C, and 2C at -20°C, and their capacity retention rates were calculated. The test method is as follows:

[0094] 1. Pretreatment at room temperature, the steps are as follows:

[0095] 1. Standard discharge: The battery is discharged at a constant current of 0.5C (A) to 2.5V;

[0096] 2. Let stand for 5 minutes;

[0097] 3. The battery is charged at a constant current and constant voltage of 0.5C (A), with a cut-off voltage of 3.65V and a cut-off current of 0.05C (A); the cycle is repeated 10 times, and the last discharge capacity is taken as the initial capacity, which is recorded as Q0';

[0098] 2. 1. Set different temperatures to -20±2℃ and leave for 0.5h;

[0099] 2. Discharge at different rates (0.5C, 1C, 2C) with a cut-off voltage of 2.5V;

[0100] 3. Record the discharge capacity Q2 of the battery and calculate the capacity retention rate = Q2 / Q0'; the results are shown in Table 1.

[0101] (III) Peel force test of modified SBR binder

[0102] GB / T2792-2014 standard is used to test the peeling force between the negative electrode active material layer and the copper foil on the negative electrode sheet of the lithium-ion battery.

[0103] (IV) Strength test of modified SBR binder

[0104] The modified SBR binders obtained in the above examples and comparative examples were naturally air-dried for 15 days at a temperature of 40° C. and a humidity of less than 20% to obtain modified SBR films, and then the tensile strength and elongation of the modified SBR films were tested respectively using GB / T 30776-2014 standard.

[0105] Table 1

[0106]

[0107] Table 2

[0108]

[0109]

[0110] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:

[0111] The modified SBR binder with the above chemical formula has a core-shell structure, wherein the inside of the shell is a cross-linked structure of styrene and amide compound copolymer molecular chains, and the outside of the shell is a hydrophilic polar group corresponding to butadiene and a rigid monomer, as well as some surfactants. The modified SBR binder with the above structure of the present application has excellent adhesion, mechanical strength and low temperature tolerance, and the above preparation method is simple and low cost.

[0112] The above are only embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A modified SBR binder, characterized in that, The chemical formula of the modified SBR binder is as follows: wherein a, b, c and x are each independently a degree of polymerization, a is 10,000 to 12,000, b is 15,000 to 20,000, c is 13,000 to 18,000, and x is 1 to 15.

2. The modified SBR binder according to claim 1, characterized in that The molecular weight of the modified SBR binder is 400,000 to 600,000.

3. The modified SBR binder according to claim 1 or 2, characterized in that, The modified SBR binder exists in the form of latex particles, and preferably the particle size of the latex particles is 50 to 150 nm.

4. A method for preparing the modified SBR binder according to any one of claims 1 to 3, characterized in that: The preparation method comprises: Step S1, mixing raw materials including an emulsion, styrene, a first initiator and an amide compound and performing a first polymerization reaction to obtain a first polymer intermediate; Step S2, subjecting the raw materials including the first polymerization intermediate, the deoxidizer, the second initiator, butadiene and the rigid monomer to a second polymerization reaction to obtain a product system; Step S3, post-processing the product system to obtain a modified SBR binder; Wherein, the rigid monomer is an organic carboxylic acid substituted with a cycloalkyl group.

5. The preparation method according to claim 4, characterized in that: In the step S1, the temperature of the first polymerization reaction is 50-80° C., and / or the time of the first polymerization reaction is 1.5-4 h; and / or the first initiator is peroxybenzoic acid ester and / or diisopropyl peroxydicarbonate; and / or the emulsion comprises an emulsifier and water, and the mass ratio of the water to the emulsifier is (200-400):(0.1-0.5), preferably (300-350):(0.2-0.4); preferably, the emulsifier is selected from any one or more of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, fatty acid soap, quaternary ammonium salt and polyol fatty acid ester; preferably, the mass ratio of the emulsifier to the first initiator is (0.1-0.5): (0.5~1.0)。 6. The preparation method according to claim 4 or 5, characterized in that: In the step S2, the temperature of the second polymerization reaction is 70 to 90° C., and / or the time of the second polymerization reaction is 2 to 4 hours; and / or the cycloalkyl substituent in the rigid monomer is C3 to C 10 The cycloalkyl group is preferably a C3-C6 cycloalkyl group, preferably a C5-C6 cycloalkyl group. Further, the rigid monomer is preferably a formic acid substituted with a C5-C6 cycloalkyl group. Further, the rigid monomer is preferably selected from any one or more of pipecolic acid, L-proline, and 2-aminocyclohexanecarboxylic acid.

7. The preparation method according to any one of claims 4 to 6, characterized in that: In the step S2, the mass ratio of the styrene, the butadiene, the amide compound and the rigid monomer is (20-25): (10-15): (1-3): (0.1-0.5), preferably (22-24): (12-13): (1.5-2.0): (0.2-0.3).

8. The preparation method according to any one of claims 4 to 7, characterized in that: The molecular weight of the amide compound is (101-300), and the amide compound is preferably selected from any one or more of N-hydroxymethyl acrylamide, N-hydroxyethyl acrylamide, N-hydroxypropyl acrylamide and N-hydroxybutyl acrylamide.

9. The preparation method according to any one of claims 4 to 8, characterized in that: The deoxidizer is bleaching powder; and / or the mass ratio of the deoxidizer to the second initiator is (0.5-1.0):(0.5-2.0); and / or the second initiator is azobisisobutyl cyanide and / or azobisisoheptanenitrile; and / or the mass ratio of the second initiator to the rigid monomer is (0.5-2):(5-10).

10. The preparation method according to any one of claims 4 to 9, characterized in that: The post-treatment is an extraction treatment.

Citation Information

Patent Citations

  • Carbon black modified water-based SBR lithium ion battery binder and preparation method thereof

    CN108598482A

  • Emulsion polymerization adhesive for lithium battery negative electrode substituted SBR (Styrene Butadiene Rubber) and preparation method thereof

    CN114478898A

  • Composite binding agent used for lithium battery and preparation method of composite binding agent

    CN109721673A

  • Adhesive as well as preparation method and application thereof

    CN113880999A

  • Modified SBR (styrene butadiene rubber) binder as well as preparation method and application thereof

    CN114478958A